Dynamic modeling and control of the tidal current turbine using DFIG and DDPMSG for power system stability analysis. (December 2016) - Aly, Hamed H.H.
Highlights: Two different types of generators and their controllers are used. The overall dynamic system of the tidal current turbine is modeled. The results show better performance of DDPMSG over DFIG. The preferred ranges of the controllers coefficients values are concluded. The most effective coefficient is concluded. Abstract: This paper describes the overall dynamic models of tidal current turbine driving either a doubly fed induction generator (DFIG) or a direct drive permanent magnet synchronous generator (DDPMSG) connected to a single machine infinite bus system including controllers to improve system stability. Testing with ranges of controller gains is carried out to establish zones of stability. The overall results show the advantages of using the DDPMSG over the DFIG. In this paper we used two different models for each machine; the full model and the reduced order model. Also IEEE-9 bus system is used in this work for multi-machine system and tested for a small signal stability analysis.